A 1463 Gene Cattle–Human Comparative Map With Anchor Points Defined by Human Genome Sequence Coordinates - Everts-van der Wind, Annelie; Kata, Srinivas R.; Band, Mark R.; Rebeiz, Mark; Larkin, Denis M.; Everts, Robin E.; Green, Cheryl A.; Liu, Lei; Natarajan, Shreedhar; Goldammer, Tom; Lee, Jun Heon; McKay, Stephanie; et al. (Genome Research, 2004)
A second-generation 5000 rad radiation hybrid (RH) map of the cattle genome was constructed primarily using cattle ESTs that were targeted to gaps in the existing cattle–human comparative map, as well as to sparsely populated map intervals. A total of 870 targeted markers were added, bringing the number of markers mapped on the RH5000 panel to 1913. Of these, 1463 have significant BLASTN hits (E < e–5) against the human genome sequence. A cattle–human comparative map was created using human genome sequence coordinates of the paired orthologs. One-hundred and ninety-five conserved segments (defined by two or more genes) were identified between the cattle and human genomes, of which 31 are newly discovered and 34 were extended singletons on the first-generation map. The new map represents an improvement of 20% genome-wide comparative coverage compared with the first-generation map. Analysis of gene content within human genome regions where there are gaps in the comparative map revealed gaps with both significantly greater and significantly lower gene content. The new, more detailed cattle–human comparative map provides an improved resource for the analysis of mammalian chromosome evolution, the identification of candidate genes for economically important traits, and for proper alignment of sequence contigs on cattle chromosomes.
10.1101/gr.2554404